(untitled) (Scientific journal of the Fergana State University, 2024)
This article is devoted to the educational possibilities of ethnopedagogical values aimed at developing a sense of national pride in students. In particular, it is aimed at revealing the educational significance of fairy tales, epics, songs, proverbs, proverbs, sayings, legends, myths and stories, which are examples of folk oral creativity, expressing the educational views of the Uzbek people.